A reevaluation of Whittle (1986, 1992) reveals the link between detection thresholds, discrimination thresholds, and brightness perception - Kane, David; Bertalmío, Marcelo (Journal of vision (Charlottesville, Va.), 2019)
In 1986, Paul Whittle investigated the ability to discriminate between the luminance of two small patches viewed upon a uniform background. In 1992, Paul Whittle asked subjects to manipulate the luminance of a number of patches on a uniform background until their brightness appeared to vary from black to white with even steps. The data from the discrimination experiment almost perfectly predicted the gradient of the function obtained in the brightness experiment, indicating that the two experimental methodologies were probing the same underlying mechanism. Whittle introduced a model that was able to capture the pattern of discrimination thresholds and, in turn, the brightness data; however, there were a number of features in the data set that the model couldn't capture. In this paper, we demonstrate that the models of Kane and Bertalmío (2017) and Kingdom and Moulden (1991) may be adapted to predict all the data but only by incorporating an accurate model of detection thresholds. Additionally, we show that a divisive gain model may also capture the data but only by considering polarity-dependent, nonlinear inputs following the underlying pattern of detection thresholds. In summary, we conclude that these models provide a simple link between detection thresholds, discrimination thresholds, and brightness perception.